2021
DOI: 10.3390/pathogens10020139
|View full text |Cite
|
Sign up to set email alerts
|

Rodent Ectoparasites in the Middle East: A Systematic Review and Meta-Analysis

Abstract: Rodents carry many ectoparasites, such as ticks, lice, fleas, and mites, which have potential public health importance. Middle Eastern countries are hotspots for many emerging and re-emerging infectious diseases, such as plague, leishmaniasis, Crimean Congo hemorrhagic fever, and Q fever, due to their ecological, socioeconomic, and political diversity. Rodent ectoparasites can act as vectors for many of these pathogens. Knowledge of rodent ectoparasites is of prime importance in controlling rodent ectoparasite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 120 publications
0
5
0
Order By: Relevance
“…The results of our study were slightly different from those of a meta-analysis that was conducted on rodent parasites in the Middle East. In our study, tick prevalence was 18%, compared to 25% in the Middle East [ 41 ]. This small difference may be explained by a different context.…”
Section: Discussionmentioning
confidence: 85%
“…The results of our study were slightly different from those of a meta-analysis that was conducted on rodent parasites in the Middle East. In our study, tick prevalence was 18%, compared to 25% in the Middle East [ 41 ]. This small difference may be explained by a different context.…”
Section: Discussionmentioning
confidence: 85%
“…However, no morphological description (in particular, how the specimens were differentiated from R. camicasi) or molecular barcode was provided for this unidenti ed Rhipicephalus sp. Overall, these studies from Arabia highlight distinct differences compared with the wider Middle East, as a recent systematic review reported that Hyalomma rhipicephaloides and Ixodes eldaricus were the most prevalent ticks found on rodents in the whole region [50].…”
Section: Discussionmentioning
confidence: 91%
“…Each species seems restricted to a specified geographical zone, with particular genera of ticks reported to act as vectors for particular Theileria sp., such as Amblyomma as a vector for T. mutans and T. velifera ; Haemaphysalis as a vector for T. orientalis , T. uilenbergi , and T. luwenshuni ; Hyalomma as vector for T. annulata , T. lestoquardi , and T. separata ; and Rhipicephalus as a vector for T. parva , T. taurotragi , T. ovis , and T. lestoquardi [ 36 ]. The MENA region has suitable climates as well as favorable conditions for the expansion of ticks and associated TBDs [ 37 , 38 ] due to widespread livestock ranching, the import of animals from other geographical territories, the wildlife population’s abundance supporting ticks’ lifecycles, and climate change conditions [ 39 ]. However, studies on TBDs within the State of Qatar are still scarce, with only reports of Hyalomma dromedarii [ 40 ], Hyalomma impeltatum [ 40 ], and more recently Hyalomma aegyptium vectors [ 41 ].…”
Section: Discussionmentioning
confidence: 99%